Advances in Metal Halide Perovskite Film Preparation: The Role of Anti‐Solvent Treatment. Issue 5 (23rd February 2021) - Sun, Jianguo; Li, Fangchao; Yuan, Jianyu; Ma, Wanli
Abstract: In the past decade, hybrid organic‐inorganic perovskite solar cells (PSCs) have attracted significant attention. Since then, the power conversion efficiency has astonishingly reached to 25.5%, situating perovskites at the forefront of all reported solution‐processed photovoltaic materials. The research of PSCs has reached a stage where efficiency, stability, and cost need to be simultaneously considered before reaching the threshold for large‐scale commercialization. In this article, the recent progress in fabricating high‐quality perovskite thin‐films adopting "anti‐solvent" strategy is reviewed and the established nucleation and crystal growth mechanisms during the treatment process is discussed. In addition, present challenges and further opportunities of the anti‐solvent methodology toward efficient and large‐scale PSCs are highlighted. The continuous efforts dedicated to the development of anti‐solvent treatment for fabricating high‐performance large‐area devices may pave the way toward commercial applications of PSCs in the near future. Abstract : The recent progress in fabricating high‐quality perovskite thin‐films adopting an "anti‐solvent" strategy is reviewed, the established nucleation and crystal growth mechanisms during the treatment process is discussed, and challenges and opportunities of the anti‐solvent methodology toward efficient and large‐scale perovskite solar cells are highlighted.